140 One step implant reconstruction in nipple sparing mastectomy: patient selection by preoperative digital mammogram. (18th September 2019) - Soderini, A; Rancati, A; Dorr, J; Gonzalez, E; Angrigiani, C; Gercovich, G; Hammond, D; Nava, M; Rocco, N; Rostagno, R
Abstract : Objectives: Background: Digital mammography clearly distinguishes gland tissue density from the overlying nonglandular breast tissue coverage, which corresponds to the existing tissue between the skin and the superficial layer of the fascia superficialis surrounding the gland (i.e., dermis and subcutaneous fat). Preoperative digital imaging can determine the thickness of this breast tissue coverage, thus facilitating planning and reducing the rate of necrotic complications after direct to implant (DTI) reconstruction in nipple sparing mastectomy (NSM). Methods: Thirty NSMs in 22 patients with type 3 tissue coverage (subcutaneous tissue thickness of 2 cm or more) were selected for DTI reconstruction after NSM to evaluate immediate skin flap/nipple areola complex ischemic complications and patient satisfaction. Results: Results: We experienced no wound healing problems or ischemic complications immediately after surgery in our population. Only 1 seroma was observed as a shortterm complication. Quality of life and patients' satisfaction level were optimal at 3 and 6 months follow-up, respectively. The aesthetic results have been evaluated as good/excellent in all cases. Conclusions: DTI immediate reconstruction with silicone implants following NSM appears to be a safe option in selected cases with enough tissue coverage, also providing a high level of patient satisfaction. The possibility of selecting cases for this procedure according to the preoperative digital mammogram showing more than 2 cm of superficial tissues thickness may help reducing the risk of immediate ischemic complications.